Kuat Tekan Dan Porositas Beton Berpori Dengan Bahan Tambah Fly Ash dan Polyester Resin - Abdurrazak Shahab; Ade Okviati Irlan; Ananto Nugroho (FORUM MEKANIKA, 2020)
The development of concrete technology in the field of civil engineering is increasingly developing. Recently, many researchers have begun to pay attention to concrete without sand or what is commonly known as porous concrete. Porous concrete is lightweight concrete because there is no fine aggregate in the mixture, so the weight of porous concrete is usually lighter than ordinary concrete. There are constituent elements of porous concrete, namely coarse aggregate and cement. The purpose of this study was to determine the compressive strength and porosity value of porous concrete with polymer-added material in the form of polyester resin so that it could be a reference for the development of porous concrete. This research was conducted by using the compressive strength and porosity test method on the variation of the porous concrete mixture that was added with polyester resin when the concrete was 28 days old. Retrieval of data from the Trisakti University concrete laboratory, which then results in the form of compressive strength and porosity values. The results of this study will show the maximum value of compressive strength obtained from the variation of the 20% Polyester Resin Pore Concrete mixture (20% BPPR) of 24.98 MPa and the maximum value of porosity obtained from the variation of the Cement Pore Concrete mixture (BPS) of 18.04%. Keywords: Compressive Strength, Porosity, Polyester Resin